Development of a Reliable Analytical Method for Liquid Anion-Exchange Extraction and Separation of Neodymium(III). (4th June 2012) - Kokare, Balasaheb N.; Kamble, Ganesh S.; Sargar, Balasaheb M.; Anuse, Mansing A.
Abstract : The liquid-liquid extraction of neodymium(III) from succinate media (0.06 M) has been studied at pH 6.0 with the solution of 0.1 M of N- n -octylaniline in xylene when equilibrium is maintained for 5 min. The back-extraction of neodymium(III) has been performed by using 0.1 M HClO4 . The effect of various parameters, such as pH, equilibrium time, extractant concentration, stripping agents, organic diluents, and aqueous to organic volume ratio on the extraction of neodymium(III) has been studied. On the basis of slope analysis, the stoichiometry of the extracted species was determined as 1 : 1 : 2 [ RR ′ NH 2 + Nd ( succinate ) 2 - ] (org) . The method is free from interference of large number cations and anions. The method was used for the selective extraction of neodymium(III) from its binary mixture with U(VI), Zr(IV), Nb(V), La(III), Th(IV), Ce(IV), and Y(III). The proposed method is selective and was successfully applied to the synthetic mixtures to show the practical utility of the extractant.